Can the Risk Factors Predicting Surgical Treatment be Determined in Patients with Tubo-Ovarian Abscess? - Vural, Tayfun; Bayraktar, Burak; Yildirim Karaca, Suna; Gurbuz, Emir; Ozeren, Mehmet; Taner, Cuneyt Eftal (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: In this study, we aimed to determine the risk factors in predicting the need for surgical treatment due to medical treatment failure in patients with tubo-ovarian abscess. STUDY DESIGN: This is a retrospective cohort study performed in a university hospital between 2015 and 2020. Sixty-nine patients with tubo-ovarian abscess were treated with parenteral antibiotics. Some of them required surgery because antibiotic treatment was not successful. We compared the group in which parenteral antibiotic treatment was successful with the group that required surgical treatment. The conservative treatment group consisted of 43 (62.3%) patients who responded to antibiotic therapy alone (gentamicin-clindamycin), and the operation group consisted of 26 women (37.7%) who did not reply to antibiotic therapy and required operation. Demographic, clinical, sonographic, and laboratory results were compared between the two groups using univariate and logistic regression analyses. RESULTS: Overall, up to 37.7% (26/69) of the patients underwent surgery after failure of antibiotic therapy. Patients who failed antibiotic therapy had higher infection parameters such as C-reactive protein (205±109 mg/dL vs. 115 ± 90 mg/dL, p=0.002), platelet count (349 ± 108 x 103/mm3 vs. 298 ± 95 x 103/mm3, p=0.042), and neutrophil-to-lymphocyte ratio (18.8 ± 35.7 vs. 8.2 ± 6.9, p=0.022). Also in the same group, larger tubo-ovarian abscess size (61.6±16.6 mm vs 45.8 ± 10.3 mm, p<0.001) and more frequent intrauterine device use (46.2% vs 16.3%, p=0.007) were observed. But none of them (C-reactive protein, neutrophil-to-lymphocyte ratio, tubo-ovarian abscess size, presence of an intrauterine device) was found to be a significant independent factor in anticipating conservative treatment failure of tubo-ovarian abscess in logistic regression analysis. CONCLUSION: Although helpful in diagnosis, none of the demographic, sonographic, or laboratory parameters can predict surgical treatment in women with tubo-ovarian abscess.